Land of the rising derivative action: Revisiting irrationality to understand Japan’s unreluctant shareholder litigant - NAKAHIGASHI, Masafumi (Institutional Knowledge at Singapore Management University, 2012)
It was not long ago that there was a consensus in the legal academy that the Japanese were irrational litigants. As the theory went, Japanese people would forgo litigating for financial gain because of their cultural obsession for maintaining social harmony. Based on this theory, it made perfect (but economically irrational) sense that Japanese shareholders let their US-transplanted derivative action lie moribund for almost four postwar decades when, at the same time, the derivative action was a staple of shareholder litigation in the United States. The 1980s brought a wave of law and economics to the scholarship of Japanese law, which largely discredited the cultural explanation for Japan’s (economically irrational) reluctant litigant. In this new academic era, reasonable minds could disagree as to whether it was the efficiency of settlement or the high cost of litigation that explained the dearth of litigation in Japan. However, the assumption that Japanese litigants were economically rational (i.e., as classical economic rational choice theory predicts, that they would litigate only when the financial benefit from doing so exceeded the cost) was virtually beyond reproach.